Analisis Manfaat Media Sosial dalam Mengembangkan Usaha Kecil Menengah : Studi pada Usaha Lapak Kece Palu - Muh Riswandi Palawa; Andi Indriani Ibrahim; Hawa Ramadani; Jumriana Elsa Safitri; Mutia Gurrata Ayyun (AKUNTANSI 45, 2026)
This study aims to explore in-depth the use of social media in the development of Small and Medium Enterprises (SMEs), with a focus on the Lapak Kece Palu Shop located in Palu City. In today’s digital era, social media not only functions as a means of communication but also a highly effective marketing tool because it can reach a wider audience at a relatively low cost. Through platforms such as Instagram, SMEs can promote products, increase interaction with customers, and strengthen brand image. This study used a qualitative descriptive method, with data collection techniques through in-depth interviews and direct observation of business owners. The results show that the use of social media, especially Instagram, plays a significant role in helping the Lapak Kece Palu Shop introduce products, expand market reach, and accelerate inventory turnover. However, obstacles were also identified such as a lack of consistency in content management and business owners’ time constraints. Based on these findings, this study provides practical recommendations for SMEs to maximize their digital marketing strategies by maintaining consistent uploads, increasing content creativity, and building active interactions with customers.